A Promoter Region Polymorphism in PDCD-1 Gene Is Associated with Risk of Rheumatoid Arthritis in the Han Chinese Population of Southeastern China. (3rd April 2014) - Liu, CuiPing; Jiang, JueAn; Gao, Li; Hu, XiaoHan; Wang, FengMing; Shen, Yu; Yu, GeHua; Zhao, ZuoTao; Zhang, XueGuang
Abstract : Objective . Programmed cell death 1 (PD-1) induces negative signals to T cells during interaction with its ligands and is therefore a candidate gene in the development of autoimmune diseases such as rheumatoid arthritis (RA). Herein, we investigate the association of PDCD-1 polymorphisms with the risk of RA among Chinese patients and healthy controls. Methods . Using the PCR-direct sequencing analysis, 4 PDCD-1 SNPs (rs36084323, rs11568821, rs2227982, and rs2227981) were genotyped in 320 RA patients and 309 matched healthy controls. Expression of PD-1 was determined in peripheral blood lymphocytes by flow cytometry and quantitative real-time reverse transcriptase polymerase chain reaction. Results . We observed that the GG genotype of rs36084323 was associated with a increased risk for developing RA (OR 1.70, 95% 1.11–2.61, P = 0.049 ). Patients carrying G/G genotype displayed an increased mRNA level of PD-1 ( P = 0.04 ) compared with A/A genotype and healthy controls. Meanwhile, patients homozygous for rs36084323 had induced basal PD-1 expression on activated CD4+ T cells. Conclusion . The PDCD-1 polymorphism rs36084323 was significantly associated with RA risk in Han Chinese population. This SNP, which effectively influenced the expression of PD-1, may be a biomarker of early diagnosis of RA and a suitable indicator of utilizing PD-1 inhibitor for treatment of RA.